2013
DOI: 10.1111/cen.12146
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and postprandial liver glycogen content in patients with type 1 diabetes mellitus after successful pancreas–kidney transplantation with systemic venous insulin delivery

Abstract: In spite of normalized glycaemic control, postprandial liver glycogen content was reduced in T1DM-PKT with systemic venous drainage. Thus, not even optimized systemic insulin substitution is able to resolve the defect in postprandial liver glycogen storage seen in T1DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This process is crucial to blood glucose homeostasis because glycaemia is maintained by degradation of hepatic glycogen during a fasting state. As reported, even optimized systemic insulin substitution cannot resolve the defect in postprandial liver glycogen storage in type I diabetic patients 5. Here, we further investigated the hepatic glucose utilization induced by Pep‐PMS in diabetic rats, including hepatic glucose uptake and hepatic glycogen production.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This process is crucial to blood glucose homeostasis because glycaemia is maintained by degradation of hepatic glycogen during a fasting state. As reported, even optimized systemic insulin substitution cannot resolve the defect in postprandial liver glycogen storage in type I diabetic patients 5. Here, we further investigated the hepatic glucose utilization induced by Pep‐PMS in diabetic rats, including hepatic glucose uptake and hepatic glycogen production.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the synthesized hepatic glycogen is responsible for the maintenance of normoglycemia between meals. As reported, subcutaneous injection of insulin cannot resolve the defect in postprandial hepatic glycogen storage in type I diabetic patients 5. Oral delivery of exogenous insulin is preferred and promising because it can simulate the biodistribution of endogenous insulin, which satisfies the high portal‐to‐peripheral gradient.…”
Section: Introductionmentioning
confidence: 99%
“…G-6-Pas and FBP-1 are key enzymes responsible for gluconeogenesis, whereas hexokinase is responsible for glucose degradation [ 41 , 42 ]. Glycogen stores are significantly depleted in the muscles and livers of T1DM animals and humans due to a lack of insulin [ 43 , 44 , 45 , 46 ]. This was also documented in the livers of the diabetic rats in this study, which also showed lower stores of hepatic glycogen.…”
Section: Discussionmentioning
confidence: 99%
“…Those with insulindependent diabetes have been found in a number of investigations, although not all, to have lower postprandial levels of hepatic glycogen than normal control subjects (9,(39)(40)(41)(42). A difference in liver glycogen levels between subjects with diabetes without complications and individuals without diabetes is most evident after the third meal of the day (40,43), and this may explain why some studies quantifying only the postbreakfast glycogen levels may not observe a difference between subjects with diabetes compared with control subjects without diabetes. It is noteworthy that normal dogs with enhanced hepatic glycogen reserves (achieved via fructose administration during an AM period of hyperinsulinemia and hyperglycemia) exhibited a markedly improved counterregulatory response (enhanced glucagon and epinephrine secretion, coupled with a stimulation of net hepatic glucose release) during a PM period of hypoglycemia in comparison with animals under the same hypoglycemic conditions but in the absence of the AM fructose infusion (10).…”
Section: Discussionmentioning
confidence: 99%